1963
DOI: 10.1039/tf9635902287
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of electron acceptors with bases. Part 10.—Complexes of polycyanobenzenes with electron donors

Abstract: The apparent association constants of N,N,N',N'-tetramethyl-p-phenylenediamine complexes with polycyanobenzenes in chlorofom have been determined spectrophotometricaly. The stabilities of similar polynitrobenzene complexes have also been measured for comparison. The polycyanobenzene complexes have lower stabilities, higher excitation energies and lower extinction coefficients than those of the corresponding nitrobenzenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1968
1968
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Mulliken correlation between the absorption band of the complexes of TMPD with XDNB molecules (black rhombuses) and halogen-free nitro- and cyanosubstituted benzenes (open rhombuses) and the LUMOs’ energies of the electron acceptors: (1) BDNB, (2) IDNB, (3) 1,2,4,5-tetracyanobenzene, (4) 1,3,5-trinitrobenzene, (5) p -dinitrobenzene, (6) m -dinitrobenzene, (7) 1,3,5-tricyanobenzene, and (8) p -dicyanobenzene. (The spectral data for TMPD complexes with 3–8 are taken from ref , and LUMO energies resulted from the DFT computations in dichloromethane. )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mulliken correlation between the absorption band of the complexes of TMPD with XDNB molecules (black rhombuses) and halogen-free nitro- and cyanosubstituted benzenes (open rhombuses) and the LUMOs’ energies of the electron acceptors: (1) BDNB, (2) IDNB, (3) 1,2,4,5-tetracyanobenzene, (4) 1,3,5-trinitrobenzene, (5) p -dinitrobenzene, (6) m -dinitrobenzene, (7) 1,3,5-tricyanobenzene, and (8) p -dicyanobenzene. (The spectral data for TMPD complexes with 3–8 are taken from ref , and LUMO energies resulted from the DFT computations in dichloromethane. )…”
Section: Discussionmentioning
confidence: 99%
“…In fact, since the middle 1950s, electron-rich aromatic TMPD molecules have been among the most common components of π-bonded donor–acceptor complexes similar to Structure I. During the last 15 years, several halogen-bonded associates between TMPD and aliphatic and aromatic iodo-and bromocarbons showing very short intermolecular N···Br or N···I contacts were described as well. As for the XDNB molecules, the structural characterization of IDNB complexes with 1,4-diazabicyclo[2.2.2]­octane and 4,4-bipyridine pointed out the ability of halodinitrobenzenes to form halogen-bonded associates. Besides, the numerous studies of molecular complexes of nitrobenzenes suggested that BDNB and IDNB molecules may participate in the π–π charge-transfer bonding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…0.4 eV discrepancy is essentially the same: E ( λ max ) for ANTH/ANTH‐5‐1 is not lower than E ( λ max ) for ANTH/TCNB by 0.2 eV, it is higher than E ( λ max ) for ANTH/TCNB by 0.2 eV. Another example is a comparison of PYRN/TCNB ( λ max =497 or 500 nm in CHCl 3 (2.49±0.1 eV)) versus PYRN/ANTH‐6‐1 ( λ max =510 nm in 1,2‐C 2 H 4 Cl 2 (2.43 eV)). The λ max values, even after adjusting for CHCl 3 versus 1,2‐C 2 H 4 Cl 2 , indicate that ANTH‐6‐1 is the stronger acceptor in solution by ca.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation that has been given for these facts (32) does not seem to be satisfactory for the n-T complexes studied, since, for a given amine, the K , follows the order of 1.2-DNB > 1.3-DNB > 1.4-DNB. The fact that both the donor and acceptor are unsymmetrical compounds suggests that there could be a preferred orientation of one molecule with respect to the other in the complex (33).…”
mentioning
confidence: 90%